Co-management of Reservoir Fisheries for Sustainable Livelihoods: Insights for Fishery Managers and Extension Professionals from Field Studies in India - L.K. Tyagi , A.S. Bisht and Amar Pal, (Indian Journal of Extension Education, 2015)
Reservoirs hold tremendous potential for inland fisheries development and offer ample scope for fish yield optimizationthrough adoption of appropriate management measures. H owever, there are several socio-economic issues involved intheir management as communities displaced due to creation of these reservoirs depend upon them for earninglivelihoods.Reservoirs hold tremendous potential for inland fisheries development and offer ample scope for fish yieldoptimization through adoption of appropriate management measures. Governance and management pattern of thesereservoirs varies in different states of India and faces several challenges including the twin pressures, to increase theproduction and productivity, and ensure sustainable livelihoods for communities dependent upon these resources. Thepresent paper while discussing these issues elaborates upon the co-management approach to address them. Citingsynthesized overall summary of the major findings of the field studies done in Northern, Central and Eastern India, thepaper elaborates upon the performance of fishing cooperative societies in co-management and conservation of reservoirfishery resources and roles played by various stakeholders and their linkages in this endeavor. The paper is based onreview of literature, secondary data from various records, and primary data gathered and detail interactions had withseveral stakeholders during field studies in four states of India namely, Madhya Pradesh, Himachal Pradesh, Uttar Pradeshand Orissa covering 57 fishing cooperative societies and 875 respondents. The findings indicated that local communitiesand their organizations (fishing cooperative societies/federations) can play important role in collective management ofreservoir fisheries under the situations where some of the facilitating conditions for promoting collective action arepresent. The paper concludes that governance and management of reservoir fisheries need to be viewed in light of therecent developments and empirical evidences made available by the social scientists in natural resource management.There is tremendous scope for innovation in their governance. Lessons drawn from successes achieved in various forms ofco-management fisheries resources, such as reported here and elsewhere across the globe, need to be incorporated indevising policies and programmes for management of reservoir fisheries. The field of fisheries management andconservation presents enormous possibilities for the extension professionals to broaden their canvas and contribute policyoriented studies to help the fisheries managers and policy makers in further improving the sector.